2019
DOI: 10.1021/acs.biomac.9b00800
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Reactive Oxygen Species Generation by Mitochondria Targeting of Anticancer Drug To Overcome Tumor Multidrug Resistance

Abstract: As a major clinical tumor chemotherapeutic burden, multidrug resistance (MDR) is often a result of up-regulation of P-glycoprotein (P-gp), which strongly enhances anticancer drug efflux. The excess mitochondrial reactive oxygen species (ROS) could not only inhibit the function of P-gp through insufficient adenosine triphosphate supply but also cause apoptosis in MDR cells. Here, we designed a mitochondria targeting nanoparticulate system (GNPs-P-Dox-GA) for overcoming MDR through enhanced ROS generation, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…4). 28 Although the chemophotodynamic therapy has a signicant synergistic effect on malignant tumors, currently available nanocarriers have limited capabilities in selective toxicity, drug release and tumor penetration. A poly ethylene glycol (PEG)stearylamine (C18) conjugate (PTS) self-assembled with ROSsensitive thioketal linker (TL), and was combined with the coloaded doxorubicin (DOX) and photosensitive decolorant A (PhA) to enhance the local chemophotodynamic therapy.…”
Section: Ros and Cancer Medicinementioning
confidence: 99%
“…4). 28 Although the chemophotodynamic therapy has a signicant synergistic effect on malignant tumors, currently available nanocarriers have limited capabilities in selective toxicity, drug release and tumor penetration. A poly ethylene glycol (PEG)stearylamine (C18) conjugate (PTS) self-assembled with ROSsensitive thioketal linker (TL), and was combined with the coloaded doxorubicin (DOX) and photosensitive decolorant A (PhA) to enhance the local chemophotodynamic therapy.…”
Section: Ros and Cancer Medicinementioning
confidence: 99%
“…Most of the PSs in WSON‐PEG 3400 and WSON‐PEG 2000 were located in the cytoplasm of the tumour cells. In particular, WSON‐PEG 3400 and WSON‐PEG 2000 displayed a mitochondria‐targeted accumulation (orange‐colour in merged images) of PSs, inducing mitochondria‐mediated apoptosis to destroy the tumour cells [22,37,47–51] …”
Section: Resultsmentioning
confidence: 99%
“…Since GA could generate hydrogen peroxide which led to the opening of mitochondrial permeability transition pore (MPTP) when Ca 2+ was also present, it might be capable of delivering drugs to IMS and matrix. Our group designed a GA-modified gelatin nanoparticle and it exhibited 4-fold higher cell internalization and 8.8-fold higher mitochondrial accumulation than GA unmodified nanoparticles in HepG2/ADR cells (details were introduced in next section) (Liu et al 2019). These results revealed that GA is a novel potentially active ligand for both hepatocellular carcinoma and mitochondria targeting.…”
Section: Small-molecule Ligandmentioning
confidence: 99%
“…Unfortunately, the positive charge of P-M-DOX restricted its application in vivo. Considering that, another smart mitochondrial targeted nanoparticle was (Zhou et al 2019) designed for better in vivo drug delivery (Liu et al 2019). As HPMA copolymer with a small size was capable of achieving deeper tumor penetration but its blood stability and tumor accumulation were unsatisfactory, HPMA copolymers modified degradable gelatin nanoparticles (GNPs) was developed as a size-switchable carrier to realize both long circulation and deep penetration.…”
Section: Mitochondrial Targeting For Overcoming Multidrug Resistancementioning
confidence: 99%